Prediction of Locoregional Control in Head and Neck Squamous Cell Carcinoma with Serial CT Perfusion during Radiotherapy - Truong, M.T. (AJNR Am J Neuroradiol, 2011)
BACKGROUND AND PURPOSE: Tumor hypoxia is a known factor of radioresistance in HNSCC. CTP is a noninvasive method of measuring tumor perfusion in vivo. The purpose of our study was to determine serial changes in tumor perfusion in HNSCC during a course of RT by using CTP and to correlate tumor perfusion measurements to LRC. MATERIALS AND METHODS: A prospective study was performed in 15 patients with HNSCC receiving definitive RT who underwent serial CTP before RT; at weeks 2, 4, and 6 of RT; and 6 weeks after RT. The median follow-up was 28 months (range, 6–44 months). Thirteen patients achieved LRC, and 2 patients had LRF. Tumor perfusion parameters, including BF, BV, MTT, and CP, were obtained by using a deconvolution-based analysis. RESULTS: Pretreatment tumor BF was significantly higher in patients who achieved LRC, 118.0 mL/100 g/min, compared with those with LRF, 53.4 mL/100 g/min (P = .004). Similarly, pretreatment CP was higher in patients with LRC, 16.6 mL/100 g/min, compared with those with LRF, 7.7 mL/100 g/min (P = .02). At week 2 of RT, tumor BF parameters showed a 27.5% increase versus an 18.1% decrease from pretreatment BF values (P = .046) in patients with LRC and LRF, respectively. A decrease in BF and BV was observed in both groups 6 weeks after RT compared with these values at baseline scanning. CONCLUSIONS: An increase in tumor BF and CP by using CTP early during a course of RT predicts LRC in patients with HNSCC treated with RT.